The cross-cultural adaptation of Chinese international students: an empirical study on sequential-mediated effects - Miao, Chenglong; Zhang, Shuai (Frontiers in Psychology, 2024)
Using convenience sampling and snowball sampling methods, data from 432 Chinese international students in 10 countries, including the United Kingdom, South Korea, and the United States, were collected to construct a multivariate sequential-mediated mixed model for cross-cultural adaptation. SPSS 23.0 and AMOS 23.0 were employed for aggregated validity, discriminant validity, and sequential-mediated effects analysis. The study found that: Cultural adaptation stress is negatively correlated with positive coping and positively correlated with negative coping, with negative coping having a significant negative impact during the cross-cultural adaptation process. Positive coping is positively correlated with sports participation, while negative coping is negatively correlated with sports participation. Sports participation is positively associated with in-group identification and negatively associated with out-group bias. In-group identification has a positive impact on cross-cultural adaptation, whereas out-group bias cannot effectively predict cross-cultural adaptation.